2023
DOI: 10.1093/jac/dkad208
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of sitafloxacin monotherapy for quinolone-resistant rectal and urogenital Mycoplasma genitalium infections: a prospective cohort study

Abstract: Background Mycoplasma genitalium has a tendency to develop macrolide and quinolone resistance. Objectives We investigated the microbiological cure rate of a 7 day course of sitafloxacin for the treatment of rectal and urogenital infections in MSM. Patients and methods This open-label, prospective cohort study was conducted at the National Center for Global He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…The GyrA-M95I mutation was rarely found in samples considered to be ParC WT or non-S83I (2.2%; 2/93). Combined with results from Hamasuna et al ., 9 which showed elevated moxifloxacin MICs (≥2 mg/L) in M. genitalium strains with concomitant ParC-S83I and GyrA mutations, and recent studies linking the presence of concurrent ParC-S83I and GyrA mutations to significantly lower cure rates with sitafloxacin and moxifloxacin, 5 , 6 this study further highlights the utility of diagnostic tests that include both ParC-S83I and GyrA-M95I for precision treatment of M. genitalium .…”
supporting
confidence: 60%
See 1 more Smart Citation
“…The GyrA-M95I mutation was rarely found in samples considered to be ParC WT or non-S83I (2.2%; 2/93). Combined with results from Hamasuna et al ., 9 which showed elevated moxifloxacin MICs (≥2 mg/L) in M. genitalium strains with concomitant ParC-S83I and GyrA mutations, and recent studies linking the presence of concurrent ParC-S83I and GyrA mutations to significantly lower cure rates with sitafloxacin and moxifloxacin, 5 , 6 this study further highlights the utility of diagnostic tests that include both ParC-S83I and GyrA-M95I for precision treatment of M. genitalium .…”
supporting
confidence: 60%
“… 4 , 5 This has been further demonstrated by recent studies from Australia and Japan, showing an increased risk of moxifloxacin or sitafloxacin treatment failure where M. genitalium harboured both the ParC-S83I mutation (G248T DNA change) and a concurrent GyrA mutation affecting M95 (particularly M95I/G285A or G285T) or D99. 5 , 6 Here, we explored the proportion of concurrent ParC and GyrA mutations in M. genitalium in Queensland, Australia, to better understand their co-occurrence and diagnostic value for resistance-guided treatment, and their potential links with specific M. genitalium genotypes.…”
mentioning
confidence: 99%
“…Unfortunately, sequencing of these samples was not available due to the impact of coronavirus disease 2019 (COVID-19) on our laboratory services over the study period, but we know that the prevalence of clinically relevant parC mutations exceeded 20% in M genitalium infections in our clinic population during this study [ 4 , 10 , 11 ]. In addition, it is anticipated that approximately 30% of M genitalium infections with a parC mutation will have a concurrent gyrA mutation, further impacting on treatment outcome [ 7 , 10 ]. Sitafloxacin cured 94% of M genitalium infections that had not previously failed moxifloxacin compared to 69% of infections that had, highlighting the value of this immediately available information to clinicians to inform of decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Sitafloxacin is a quinolone that is available across the Asia-Pacific region but is limited elsewhere. In Japan, sitafloxacin has been used for a number of years as monotherapy for M genitalium and was reported to achieve cure of approximately 90% [ 6 , 7 ]. However, in Australia, due to concerns about antimicrobial stewardship, sitafloxacin is now reserved for the treatment of resistant M genitalium infections.…”
mentioning
confidence: 99%
“…Given the unavailability of resistance testing for MRMs and the high prevalence of strains harboring MRMs (89.6%), sitafloxacin is the preferred treatment for M genitalium infections at our facility. Ando et al [ 20 ] reported that sitafloxacin monotherapy cleared strains harboring wild-type parC and gyrA . In addition to resistant strains, sitafloxacin demonstrated high effectiveness (92.9%) in clearing strains harboring parC G248T (S83I) mutations and wild-type gyrA , with 41.7% of those harboring parC G248T (S83I) and gyrA mutations.…”
Section: Introductionmentioning
confidence: 99%